The secret world of bats - Plage, Dieter; Tuttle, Merlin D.; Linley, Mike.; Creelman, Graham; Keach, Stacy; Survival Anglia Ltd.; Bat Conservation International (Austin, Tex. : Bat Conservation International, 2005)
Cinematographer Dieter Plage follows Bat Conservation International founder Merlin Tuttle across five continents, capturing all aspects of bat behavior with slow-motion photography. You'll see bats courting, rearing their young, and hunting prey. You'll witness the symbiosis between bats and desert cacti, tropical rain forest trees and the African baobab "tree of life." You'll meet bat conservationists the world over, from Thai monks to Australia's "bat mums."
DVD.
Host: Stacy Keach.
Executive producer, Graham Creelman ; camera, G. Dieter Plage ; scientific advisor, Merlin D. Tuttle ; film editor, Leslie Parry ; music, Guy Michelmore.
DVD release of the program originally shown on CBS television.
Keywords: Bats; Wildlife conservationists; Wildlife films; Documentary films